Optimized Inner-Volume 3D TSE for High-Resolution Vessel Wall Imaging of Intracranial Perforating Arteries at 7T - Kong, Qingle; Wu, Yue; Weng, Dehe; An, Jing; Zhuo, Yan; Zhang, Zihao (Frontiers in Neuroscience, 2021)
The impairment of microvessels can lead to neurologic diseases such as stroke and vascular dementia. The imaging of lumen and vessel wall of perforating arteries requires an extremely high resolution due to their small caliber size. Current imaging techniques have the difficulty in observing the wall of perforating arteries. In this study, we developed a 3D inner-volume (IV) TSE (SPACE) sequence with optimized 2D spatially selective excitation (SSE) RF pulses. The optimized SSE RF pulses were designed through a series of optimization including iterative RF pulse design, trajectory optimization, and phase convention of Carr-Purcell-Meiboom-Gill (CPMG) condition to meet the perforating arteries imaging demands. High resolution of isotropic 0.30mm within ten minutes was achieved for the black- blood images of lenticulostriate artery (LSA). The LSA lumen and vessel wall were imaged by the IV-SPACE sequence simultaneously. Images obtained by the optimized RF pulse has fewer aliasing artifacts from outside of ROI than the traditional pulse. The IV-SPACE images showed clearer delineation of vessel wall and lumen of LSA than conventional SPACE images. IV-SPACE might be a promising method for detecting microvasculopathies of cerebral vascular diseases.